Next-Generation Sequencing Analysis Reveals Frequent Familial Origin and Oligogenism in Congenital Hypothyroidism With Dyshormonogenesis - Oliver-Petit, Isabelle; Edouard, Thomas; Jacques, Virginie; Bournez, Marie; Cartault, Audrey; Grunenwald, Solange; Savagner, Frédérique (Frontiers in Endocrinology, 2021)
Context: Congenital hypothyroidism (CH) is related to dyshormonogenesis in 15 to 40% of the world population and associated with homozygous or heterozygous variants in the main genes of the hormone synthesis pathway. Emerging diagnostic tools such as next generation sequencing (NGS) have been used to efficiently explore panels of genes and identify complex mechanisms of pathogenesis. Objective: We explored 19 candidate genes known to be causative for permanent or transient CH to evaluate the role of complex gene variations in CH phenotype. Patients, design and setting: Using the NGS approach, we studied 65 newborns with thyroid dyshormonogenesis (TDH). New variants were assessed in silico for pathogenicity. Results: Among the 65 infants, 56.9% presented a variant in one or more genes of the thyroid hormone synthesis axis. We identified homozygous or compound heterozygous variants in the TG, DUOX2, TPO or SLC5A5 genes in 10 infants and heterozygous variants in DUOX2, TG, TPO and TSHR in 19 others. In 7 cases, a heterozygous variant in the TG gene was the unique anomaly detected, but related to disturbed hormonal balance. Oligogenic variants were found in 8 infants associated with severe CH and goitre in 5 of them. Conclusion: The systematic exploration of genes involved in thyroid hormone synthesis by NGS in TDH showed high diagnostic relevance. Oligogenic inheritance could be related to phenotypic heterogeneity and a high frequency of goitre.